Prevalence and predictors of hardcore smoking in India-: Findings from the global adult tobacco survey (2016-2017) - Sitikantha Banerjee; Jaya P Tripathy; Kajari Bandyopadhyay; Pradeep Deshmukh (Wolters Kluwer Medknow Publications, 2021)
Background: Hardcore smokers are of significant public health concern having a greater risk of developing tobacco-related diseases. Objective: This study aimed to identify burden of hardcore smokers, its distribution, and determinants in India. Subjects and Methods: Analysis of Global Adult Tobacco Survey India 2016-2017 data was carried out. Hardcore smoking was defined when the following criteria were fulfilled - current daily cigarette smoking for at least 5 years, no quit attempt in past 12 months, no intention to quit in next 12 months, and time to first smoke within 30 min of waking up. Independent variables included sociodemographic, knowledge of side effects, indoor smoking policy, and age of smoking initiation. Multivariable logistic regression was carried out, with adjustment for clustering, stratification, and sampling weight. Results: Proportion of hardcore smoking among the general population and current daily smokers were 3.43% and 32.3%, respectively. In the adjusted model, it was found to be significantly associated with increasing age, earlier initiation of daily smoking, tribal caste, and unfavorable indoor smoking policy. Conclusion: Tobacco control strategies should be modified to tackle these issues, especially early age of initiation of daily smoking and indoor smoking policy.